Kitab Kumpulan Ringkas Berbetulan Lekas: Karya ketatanegaraan Melayu yang terakhir - Jelani Harun, (Universiti Kebangsaan Malaysia, 2001)
The genre of Mirrors for Rulers is a salient feature in traditional Malay literature. Until recently, it has not been studied fully. Many Malay literary works not only depict the authors’ interest in Mirrors for Rulers, but also reveal forms of interaction between the Malay traditional value and value of other culture, in particular those on Islamic thoughts and principles. The main aim of such an undertaking is to show how Malay rulers and ministers should behave in dealing with their subjects especially in terms of the deed of justice. One example may be seen in the Kitab Kumpulan Ringkas Berbetulan Lekas, written by Raja Haji Ali Kelana